Misunderstanding and Writing Signs in Mathematical Proof - Aziz, Abdul; Suprayitno, Iswahyudi Joko (Education, Science, and Technology International Conference, 2024)
Mathematical proof is an important ability in studying mathematics. The aim of this research is to find out errors in writing mathematical signs. The mathematical signs or symbols used are related to group proofs. The research method used was qualitative research involving four universities. The research results showed that there were errors in writing signs caused by not knowing the concept of group proof correctly. Writing correct signs in mathematical proof has an important role. Errors in writing mathematical signs can cause the process of mathematical proof to become unclear.